If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying u + 2 = 0 Reorder the terms: 2 + u = 0 Solving 2 + u = 0 Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + u = 0 + -2 Combine like terms: 2 + -2 = 0 0 + u = 0 + -2 u = 0 + -2 Combine like terms: 0 + -2 = -2 u = -2 Simplifying u = -2
| 3u^2-3= | | 8a+24b= | | (8x+6)+(x+5)= | | u^2-25= | | y=4mx+2b | | 3u-21= | | y=5mx-7b | | 8w+40= | | 2=-4(1-3j)+3(5j-7) | | w^2+3w-10= | | 2=-4(1-3j)+(5j-7) | | 5n^2+35n=0 | | -19=8(g-3)-5(-3+2g) | | (y^2-11y+30)(5y+10)=0 | | 2(x-2)+15=14 | | 8(n-4)-7(n+8)=-80 | | 15x^2+4xy-4y^2= | | 10x+2x+8x-7x+17(x-1)=43 | | 8(h-4)-7(h+8)=-80 | | 7n^2-20n-32=0 | | 2x^2+3xy-35y^2= | | 2x^2+19xy+35y^2= | | n^2*n^8= | | -7+5x=-42 | | x^3-18x^2+432= | | s^2-2s-63= | | 10+4a=-6 | | 9x^2+81x=0 | | 2m+1=9 | | 12+6x=-54 | | b^2-13b+40=0 | | x^2+18x-225=0 |